2007
DOI: 10.3390/medicina43090092
|View full text |Cite
|
Sign up to set email alerts
|

Brain natriuretic peptide and other cardiac markers predicting left ventricular remodeling and function two years after myocardial infarction

Abstract: Background. Left ventricular remodeling is a complex pathologic process of progressive left ventricular dilatation, leading to dysfunction and heart failure in patients after myocardial infarction. Objective. To evaluate biochemical markers, reflecting cardiac remodeling process after first myocardial infarction and compare those markers with clinical characteristics of left ventricular remodeling. Material and methods. Brain natriuretic peptide, troponin I, creatine kinase, creatine kinase MB mass, lactate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Experimental studies have shown that the level of BNP secretion and BNP mRNA expression are high mainly in the boundary region between the infarcted and non-infarcted regions (Hama et al 1995) that is stimulated by the increased wall stress that directly related to the infarction. Also it was found that BNP level following MI appears to be associated not only with left ventricle ejection fraction (LV-EF) deterioration, but also with the extent of myocardial injury as assessed by cardiac markers, supporting the opinion that elevation of BNP is a general indicator of reduced cardiac performance (Grybauskiene et al 2007). In a previous study, high plasma BNP levels 3 months after optimized treatment for HF are risk factors for morbidity and mortality of patients with HF; moreover, plasma BNP levels 3 months after optimized treatment are more useful predictors than the levels of LV-EF (Maeda et al 2000).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Experimental studies have shown that the level of BNP secretion and BNP mRNA expression are high mainly in the boundary region between the infarcted and non-infarcted regions (Hama et al 1995) that is stimulated by the increased wall stress that directly related to the infarction. Also it was found that BNP level following MI appears to be associated not only with left ventricle ejection fraction (LV-EF) deterioration, but also with the extent of myocardial injury as assessed by cardiac markers, supporting the opinion that elevation of BNP is a general indicator of reduced cardiac performance (Grybauskiene et al 2007). In a previous study, high plasma BNP levels 3 months after optimized treatment for HF are risk factors for morbidity and mortality of patients with HF; moreover, plasma BNP levels 3 months after optimized treatment are more useful predictors than the levels of LV-EF (Maeda et al 2000).…”
Section: Discussionmentioning
confidence: 81%
“…In addition, BNP is not considered released from the necrotizing myocardium (Grybauskiene et al 2007). Experimental studies have shown that the level of BNP secretion and BNP mRNA expression are high mainly in the boundary region between the infarcted and non-infarcted regions (Hama et al 1995) that is stimulated by the increased wall stress that directly related to the infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The results are shown in Figure 1. The other researchers have got results of BNP and troponin correlation with correlation coefficient r = 0.273-0.70 (15,19). Necrosis and apoptosis of myocytes in AMI are contributions of progressive left ventricle dysfunction.…”
Section: Resultsmentioning
confidence: 96%
“…Because natriuretic peptides (NPs) are produced in the heart, they may serve as a biological marker of LV remodeling and changes in circulating NPs may parallel the changes in LV structure [6-8]. …”
Section: Introductionmentioning
confidence: 99%